Novel selective and potent 5-HT reuptake inhibitors with 5-HT1D antagonist activity: chemistry and pharmacological evaluation of a series of thienopyran derivatives - Torrado, Alicia; Lamas, Carlos; Agejas, Javier; Jiménez, Alma; Dı́az, Nuria; Gilmore, Jeremy; Boot, John; Findlay, Jeremy; Hayhurst, Lorna; Wallace, Louise; Broadmore, Richard; Tomlinson, Rosemarie (Bioorganic & medicinal chemistry, 2004)
A series of compounds combining the naphthylpiperazine and thienopyran scaffolds has been prepared and evaluated for 5-HT reuptake inhibition with 5-HT1D antagonist activity. The design of these compounds has been based on the 'overlapping type' strategy where two pharmacophores are linked in a single molecule. The resultant dual pharmacological profile has the potential to deliver a more efficient treatment for depression.